"I Know That My Redeemer Liveth": Schreber and the Matter of Music. (2nd October 2022) - Stoholski, Mark
Abstract : For Imre Hermann, a central figure of Hungarian psychoanalysis, the aesthetic relation to music, entailing an objectless, affect-laden situation, offers a privileged point for understanding infantile sexuality and its reemergence in regressive states. Schreber's Memoirs of My Nervous Illness, a text permeated with music, drew Hermann's interest as a model for comprehending psychotic regression. Building upon Hermann's observations, it is argued that music becomes a contested means to give form to affect where language is compromised. Within the throes of psychotic regression where there is no third and representation is experienced as violent and perverse, the aesthetic relation becomes a means of survival.